2022
DOI: 10.1364/oe.471368
|View full text |Cite
|
Sign up to set email alerts
|

Fabry-Pérot resonant avalanche-mode silicon LEDs for tunable narrow-band emission

Abstract: We report on the effect of Fabry-Pérot (FP) resonance on hot-carrier electroluminescence (EL) spectra and the optical power efficiencies of silicon (Si) avalanche-mode (AM) LEDs in the wavelength range from 500 nm to 950 nm. The LEDs, fabricated in a silicon-on-insulator photonics technology, consist of symmetric p-n junctions placed within a 0.21 µm thick Si micro-ring of varying width and radius. We show that the peak wavelength in the EL-spectra can be tuned within a range of 100 nm by varying the ring widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In 2000, Pavesi et al first reported on the nc-Si optical gain and stimulated emission at room temperature, and it is expected to become an efficient luminescent material [ 6 ]. Obtaining more suitable Si-based luminescent materials and improving the related fluorescence quantum efficiency has been one of the most difficult tasks in this field for more than two decades [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Pavesi et al first reported on the nc-Si optical gain and stimulated emission at room temperature, and it is expected to become an efficient luminescent material [ 6 ]. Obtaining more suitable Si-based luminescent materials and improving the related fluorescence quantum efficiency has been one of the most difficult tasks in this field for more than two decades [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%